DISEASES OF CORN IN MEXICO - NIEDERHAUSER, JOHN S (Hospital Spanish, CD MEXICO, DF, MEX, 1979)
The work deals with both the chemical and electrical mechanisms of nerve impulse transmission, being distinctive in its discussion of the role of acetylcholine as the chemical mediator at autonomic ganglia and at neuro-muscular junctions The book is divi
PHYS REV B
Keywords: DISEASES, CORN, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL